One million - Hendrik Hertzberg (Abrams Image, 2009)
Originally published in 1970, One Million has been out of print for some time, and its author, the highly esteemed New Yorker editor and columnist Hendrik Hertzberg, has been prompted by fans to create a new edition. Originally, the project was inspired by the author's journalistic impulse to try to make the newsworthy, large, and rather abstract number more concrete for people. To that end, he has created a book in which each of the 200 pages features five thousand dots, but on each page, a few of the dots are called out from their place in numerical order with a little piece of statistical information that add up to really bring the concept home.